The effect of vitamin E, selenium, and copper supplementation preweaning on the performance and immune response of beef calves - Wright, C.L.; Corah, L.R.; Stokka, Gerald L.; Blecha, Frank; Lynch, G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were conducted to determine the effect of vitamin E, selenium, and copper supplementation on the pre- and postweaning performance, immune responses, and serum metabolites o f crossbred beef calves. In experiment 1, 71 calves were blocked by weight and allotted to one of four individually fed treatments: 1) control supplement (2 lb grain creep ) (CS), 2) CS + .27 mg selenium + 500 IU vitamin E, 3) CS + 9.1 mg copper, and 4) combination of treatments 2 and 3. In experiment 2, 80 crossbred beef calves were blocked by weight and allotted to 5 individually fed treatments: 1) control supplement (2 lb grain creep) (CS), 2) CS + .27 mg selenium, 3) CS + .27 mg selenium + 500 IU vitamin E, 4) CS + .27 mg selenium + 1000 IU vitamin E, and 5) CS + .27mg selenium + 1500 IU vitamin E. Supplements were fed daily on an individual basis. In experiment 1, vitamin E supplementation reduced plasma haptoglobin levels by the end of the study and tended (P=.11) to improve postweaning gain. However, no other effect was noted on calf performance or immune parameters in either experiment.
Keywords: Beef; Vitamin E; Selenium; Copper; Suckling calves; Growth; Health; Immune system